The impact of digitalization on current marketing strategies - Matosas-López, Luis (Marketing & technology: new horizons and challenges, 2024)
Digitalization has completely transformed marketing. It has changed consumption habits, consumer behaviour, and purchasing processes. In addition, it has modified marketing strategies, tactics, and processes, offering a wide range of mechanisms that allow companies, of all types and sizes, to enhance their commercial actions. The Impact of Digitalization on Current Marketing Strategies is the first volume in the Marketing and Technology: New Horizons and Challenges series. This publishes cutting-edge, high-quality, and original contributions that present results, theories, concepts, models, and applications of the latest technologies throughout the marketing domain. Subjects covered in this volume include the rise of social media as a marketing tool, customization of the online user experience, pricing strategies in the digitalization era, privacy and ethical considerations in the digital setting, the use of CRM solutions for customer-centric strategies, the importance of corporate digital responsibility, the role of social media influencers, or the use of AI and chatbots to interact with customers. Series editor Luis Matosas-López provides multidisciplinary references for researchers, instructors, and professionals interested in the most up-to-date research on the challenges connected with the expanding ground of digitalization and marketing.